The development of the school newspaper in Israel between 1948–1980: concept and product - Dahan, Ilana (CEP USM, 2023)
Hebrew media has a rich history which continued to be produced after the creation of the state of Israel in both formal and informal settings. The production of school newspapers influences the extracurricular educational activity by enriching it with valuable content, as well as the spirit, that is useful for the harmonious development of the students involved in such activities. The process of designing and producing school newspapers between 1948 and the eighties of the 20th century in Israel was carried out in a very similar way to the way in which this process was carried out in the period before the establishment of the state of Israel and continued to function in accordance with the activity of the three categories of staff usually involved in the process of making these journalistic products: teaching staff, students, as well as the category combined between the two ones. Through the research presented below, it was concluded that over the years, the editorial policy of the school newspaper in Israel was often dictated by the type of school, the religion of those involved in the process, the gender of the authors (boys, girls), age, product financing, etc. The positive aspect of the process of creating a school newspaper can also be extracted from the fact that two categories were always involved in the process of creating a school newspaper: students and teachers, the tandem working more efficiently than in other cases where only one category was involved: either only teaching staff, or only students.

Mass-media ebraică are o istorie bogată, la fel precum și ziarele școlare din Israel, care au continuat să fie realizate și după crearea statului Israel în medii formale, cât și informale. Producerea de ziare școlare influențează activitatea educațională extrașcolară prin îmbogățirea acesteia cu conținut valoric și spiritual util dezvoltării armonioase a elevilor implicați în astfel de activități. Procesul de concepere și realizare a ziarelor școlare între anii 1948 și anii optzeci ai secolului XX în Israel s-a desfășurat într-un mod foarte asemănător modului în care s-a desfășurat acest proces și în perioada anterioară înființării statului Israel. În proces erau implicate, de obicei, trei categorii de personal: personal didactic, elevi, precum și categoria combinată între primele două. Prin intermediul cercetării expuse mai jos, s-a ajuns la concluzia că de-a lungul acestor ani, politica editorială a ziarului școlar în Israel a fost adesea dictată de tipul de școală, de religia celor implicați în proces, de genul autorilor de produse (băieți, fete), de vârsta acestora, de finanțarea produsului, etc. Aspectul pozitiv al procesului de realizare a unui ziar școlar poate fi extras și din faptul că în procesul de realizare a unui ziar calitativ erau implicate cele două categorii: elevi și profesori, tandemul funcționând mai eficient decât în alte cazuri unde era implicată doar o singură categorie: fie doar personal didactic sau doar elevi.
Evoluția ziarului școlar în Israel în perioada 1948-1980: concept și produs
Keywords: mass media; school newspaper; editorial policy; educational activity; teaching staff; freedom of expression; Israel; mass-media; ziar școlar; politică editorială; activitate educațională; personal didactic; libertatea de expresie; Israel